Brainstorming Strategies in Integrating Education System for Better Technology-Based Support Learning - V. Vivek; T. R. Mahesh; G. Sindhu Madhuri (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Technology-based support learning is very important since 21st century has a growth in transforming various skills on gaining knowledge, gaining experience in electronic technology and gaining learning process digitally. Learning and teaching is not a new challenge integrated education system. As per the learners need, technology-based learning can play different delivery methods and is classified into two types synchronous delivery methods and asynchronous delivery methods. In today’s trend, there is a rapid change in education, technology and tools which require training programs to become knowledgeable workers in industry. Now a day, Technology-based learning in education system is facing few side effects like too much use of technology is leading to various security issues, face-to-face interaction issues, assessment issues, research gap, health issues like tensions and learning approaches. As the learning skills and teaching styles can improve education system effectively, most of the technological tools or brainstorming strategies help to contribute new learning skills and teaching styles in integrating education system for better growth in today’s real life. Based on today’s growth in curriculum most of the universities, the technology-based support learning system should improve with no side effects in primary education, secondary education, undergraduate and post graduate programs to students or learners. So, there should be focus more on brainstorming strategies in this integrating education system by introducing a framework based on current strategies.